2022
DOI: 10.1093/ageing/afac200
|View full text |Cite
|
Sign up to set email alerts
|

How do predisposing factors differ between delirium motor subtypes? A systematic review and meta-analysis

Abstract: Background Delirium is a common neurocognitive disorder in hospitalised older adults with vast negative consequences. The predominant method of subtyping delirium is by motor activity profile into hypoactive, hyperactive and mixed groups. Objective This systematic review and meta-analysis investigated how predisposing factors differ between delirium motor subtypes. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The barriers to assessment and practice, the influencing factors, and details in practice progress also need to be considered. Previous studies have shown that there are significant differences in the predisposing factors, etiology, treatment and outcomes among each subtype ( 56 58 ). It is necessary to clarify nurses' KAP status in subtype assessment to make subtype management protocols in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The barriers to assessment and practice, the influencing factors, and details in practice progress also need to be considered. Previous studies have shown that there are significant differences in the predisposing factors, etiology, treatment and outcomes among each subtype ( 56 58 ). It is necessary to clarify nurses' KAP status in subtype assessment to make subtype management protocols in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Those that developed hyperactive delirium were more likely to be younger, male, and have higher cognitive scores. 31 However, that review included studies that varied considerably in the reasons patients were hospitalized, including cancer, cardiac surgery, stroke, palliative care, urgent and elective surgeries, etc. In addition, prior studies used different methods for assessing delirium including the Richmond Agitation Sedation Scale and the Delirium Motor Subtype Scale which focus on symptoms of agitation and level of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…They found that patients who had hypoactive delirium were older, had poorer cognitive functioning, and higher risks scores than those with hyperactive delirium. Those that developed hyperactive delirium were more likely to be younger, male, and have higher cognitive scores 31 . However, that review included studies that varied considerably in the reasons patients were hospitalized, including cancer, cardiac surgery, stroke, palliative care, urgent and elective surgeries, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have looked to break delirium down into motor subtypes as a way of facilitating more accurate diagnosis and management. 18 , 19 Hypoactive delirium has been associated with older age, increased medication exposure, increased risk of being missed or misdiagnosed and a greater risk of morbidity and mortality, while hyperactive delirium has been linked to younger patients and carries a better prognosis. 18 It is therefore important to establish whether motor subtype differ in those with an underlying dementia, as this is a vulnerable group where delirium assessment and management can prove particularly challenging.…”
Section: Introductionmentioning
confidence: 99%